SUSTAINABILITY REPORTING IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Irma Hidayati (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2023)
The goal of this study is to find out what has happened and what can be done in the future to improve the reporting on sustainability in Indonesia. Over the past few years, the country has started to develop and implement comprehensive reporting on sustainability. Through various standards, authorities can now effectively benchmark the reports of companies on sustainability. One of these is the regulation issued by the POJK, which requires organizations to submit reports on time and in compliance with the requirements. This has encouraged more researchers to examine sustainability issues. The study was conducted through a systematic review process that was carried out by the PRISMA flow diagram. It covered over 30 papers from 2018 to 2022. The main findings of the review provide a comprehensive view of the trends in the field of research. It also offers recommendations for future studies. The researcher then categorized the research topics into three main themes: sustainability, diversity, and firm value.